Stress Analysis of the Sugar Beet Lifter with the Finite Element Method (FEM) (Agricultural Engineering, 2019)
The article presents the method of creating a 3D model of a passive lifter with (polder) plowshares, used in sugar beet harvesters, along with stages of its preparation and results of stress analysis. The computer simulation takes into account force timelines obtained during field tests of the tool. The Stress analysis module of the Autodesk Inventor program was used for the analysis, using the finite element method (FEM). The analysis included the elements that constitute the working part of the lifter, whereas elements of the flexible system were omitted. The results confirm that the lifter structure was developed correctly in terms of durability. The highest reduced stresses, calculated according to the Huber-Mises-Hencky (HMH) hypothesis, were 128.4 MPa (the minimum value of the safety factor related to the yield point is 1.61). The paper also discusses the construction of two flexible couplings with infinitely variable torsional stiffness, which can be used as an alternative solution for a typical flexible system: a shock absorber and a helical spring.